Slow and incomplete histological and functional recovery in adult gluten sensitive enteropathy. Issue 8 (August 1988) - Grefte, J M; Bouman, J G; Grond, J; Jansen, W; Kleibeuker, J H
Abstract : To assess the course of recovery of gluten sensitive enteropathy in adults, histological and functional recovery was studied in 22 patients, aged 20-79 years. Biopsy specimens taken at the time of diagnosis were studied in 20; after adhering to a gluten free diet for nine to 19 (mean 14) months in 14; and after adhering to the same diet for 24-48 (mean 34) months in 10 patients. Histological recovery was assessed morphometrically in the proximal jejunum. Mucosal linings significantly improved over time, but did not completely return to normal with a gluten free diet: at diagnosis the surface: volume ratio was 22% of normal, increasing to 48% and 66% after nine to 19 and 24-48 months, respectively, of a gluten free diet. Disaccharidase activities progressively increased. After 24-48 months maltase, sucrase, and isomaltase had returned to normal in the proximal jejunum; they were still significantly decreased in the distal duodenum. Duodenal and jejunal lactase activities were both below normal after 24 to 48 months. It is concluded that recovery of the intestinal mucosa of adults with gluten sensitive enteropathy during a gluten free diet continues beyond nine to 19 months and is still incomplete after two to four years. The recovery of disaccharidase activities extends from the distal to the proximal part of the small intestine, and is aligned to histological recovery.